Association of seizure duration and outcome in refractory status epilepticus - Madzar, Dominik; Geyer, Anna; Knappe, Ruben U.; Gollwitzer, Stephanie; Kuramatsu, Joji; Gerner, Stefan; Hamer, Hajo; Huttner, Hagen (Journal of Neurology, 2016)
The aim of the study was to identify factors influencing long-term outcome and to evaluate the prognostic power of the Status Epilepticus Severity Score (STESS) in refractory status epilepticus (RSE). We retrospectively extracted data on baseline characteristics, RSE details, and hospital course including complications from all patients treated for RSE in our institution between January 2001 and January 2013. Functional outcome was assessed using the modified Rankin Scale (mRS) and was defined as good when either RSE did not lead to functional decline or when the resulting mRS score was 2 or below. Seventy-one episodes in 65 patients were analyzed. The median follow-up time was 12 weeks (IQR 6-35), two patients were lost to follow-up. Poor functional long-term outcome was observed in 42/69 (60.9%) episodes. In-hospital mortality occurred in 13/71 (18.3%) episodes. Multivariable analysis revealed that STESS >= 3, longer RSE duration, and sepsis were independently related to poor functional long-term outcome. Receiver operating characteristics (ROC) curve analyses confirmed the cut-off dichotomization into STESS >= 3 and STESS < 3 for optimal discrimination between good and poor outcome (AUC = 0.671, p = 0.002, YI = 0.368, NPV = 0.607, PPV = 0.756) and revealed an RSE duration of 10 days as a significant cut-off point associated with outcome (AUC = 0.712, p = 0.012, YI = 0.310; NPV = 0.545, PPV = 0.750). In conclusion, STESS and RSE duration represent relevant scores and parameters impacting long-term outcome after RSE. A shorter RSE duration is associated with better outcome and, therefore, rapid and adequate treatment for seizure termination should be enforced.
EVALuna2:22460

Effects of clobazam for treatment of refractory status epilepticus - Madzar, Dominik; Geyer, Anna; Knappe, Ruben U.; Gollwitzer, Stephanie; Kuramatsu, Joji; Gerner, Stefan; Hamer, Hajo; Huttner, Hagen (BMC Neurology, 2016)
Clobazam (CLB) is a well characterized antiepileptic drug (AED) that differs from other benzodiazepines by its basic chemical structure and pharmacodynamic properties. Only one previous study examined the efficacy of CLB as add-on therapy in refractory status epilepticus (RSE).We analyzed RSE episodes treated in our institution between 2001 and 2012. Successful treatment with CLB was scored if CLB was the last AED added to therapy before RSE termination. We assessed the differences between patients with and without CLB and correlated CLB with outcome. Among patients treated with CLB, we studied responders and non-responders and compared our CLB cohort with recently published data.CLB was part of the AED regimen in 24/70 (34.3 %) RSE episodes. In six of these (25.0 %) RSE resolution was attributed to CLB. Baseline characteristics of episodes with and without CLB treatment showed no significant differences and RSE termination rates were very similar (83.3 % vs. 80.4 %). CLB was administered in clinically more complex RSE with longer RSE duration and worse outcome, but CLB was not related independently to outcome. Comparison of our results with previously published data revealed that baseline characteristics as well as CLB maintenance doses and time of treatment initiation were similar in both cohorts. CLB was less frequently the last AED added to RSE therapy in our patients indicating a lower treatment success rate than previously reported.CLB represents a reasonable AED and promising add-on agent for treatment of RSE. However, rates of successful CLB response were substantially lower than in a recently published study. Differing RSE characteristics and treatment strategies may account for the discrepancy between study results, as RSE etiologies and seizures types associated with unfavorable prognosis were more common in our cohort, while anesthetics tended to be less frequently applied to achieve seizure control.
EVALuna2:22479